Ánálise de alterações no gene receptor de andrógeno em homens com infertilidade idiopática - MESQUITA, Wyara Elanne de Jesus Castro (2009)
Male idiopathic infertility is related to defects in normal spermatogenesis, due to genetic causes. The spermatogenesis is a dependent process on high levels of male sex hormones, the androgens. The androgen, in turn, perform its function when associated with the androgen receptor (AR), protein encoded by AR gene. Mutation in AR gene lead to a synthesis of non functional AR, which results in the failure of the process of spermatogenesis and, consequently, causes male infertility. This work has as its main objective the verification of the occurrence of mutation in the AR gene in patients with male idiopathic infertility who come from the HC-UFG Human Reproduction Center. Samples were analyzed from 206 patients. The result was that 95 patients were found to be normal while 111 with an altered result for the spermogram. The samples were amplified for exons 1, 4, 6, 7 and 8 of the AR gene and the results subjected to statistical analysis, Mann Whitney, logistic regression, and chi tests. The existence of the relationship between defects of sperm and AR gene mutation was verified. The analysis of the relationship between the spermogram and the AR gene mutation in five evaluated exons was significant only for exons 1 and 7. Patients with numerical unsettled spermogram had a higher frequency of mutations in exon 7, teratozoospermics in exon 1 and exon 7 in astenozoospermics patients. Exons 4, 6 and 8 showed no meaningful statistical relationship in reference to the alteration of the spermogram. Among results related to social custom, alcohol proved to be significant for mutation in the AR gene. This study has reaffirmed the relationship between the presence of mutation in AR genes as probable causes of defects in spermatogenesis. Consequently, male idiopathic infertility depends not only on the genetic factor, but also on the association between this factor and the environment where man inhabits